Dynamic Relationship Between the Spot and Futures Markets : Empirical Evidence From Malaysian Crude Palm Oil and Stock Index Futures - Mariady, Jenny (2014)
The dynamic relationship, specifically the long-run and short-run association between the spot and the futures market has been empirically investigated in this study. Utilizing data from two of the most actively-traded futures market in Malaysia, FCPO with maturities of spot-month, 1-, 2-, 3- and 4-month futures prices and FKLI with maturities of spot-month, next-month, next-quarter and next 2-quarter futures prices, the price discovery role of futures market has been examined. The results show that all futures prices of different maturities possess long-run, equilibrium relationship with the spot prices in the context of CPO market. For stock index, it is found that long-run convergence is achieved between the spot price and spot-month futures price, 1-month futures price and next-quarter futures price respectively. The less-traded and illiquid next 2-quarter FKLI contract could be a possible justification for the rejection of the price discovery role of that particular futures contract whereby the spot leads the futures. It is also found that the spot-month futures price series responded more effectively in restoring equilibrium following a shock to the system in the long run for both markets. In the short run, it is found that there exists a bi-directional relationship between the spot and futures market for both FCPO and FKLI analysis. Nevertheless, the study has shown that the well-known, fundamental financial theory known as Efficient Market Hypothesis (EMH), which argues on the absence of lead-lag relationship between the spot and futures market has been consequently rejected. Investors could then use futures prices as unbiased predictors of future spot prices. In short, the price discovery role of Malaysian futures market has been confirmed and the introduction of futures market as a risk management tool for investors is therefore, justified.